Pengaruh Jasa Pelayanan dan Variasi Produk terhadap Partisipasi Anggota dan Sisa Hasil Usaha pada Koperasi Serba Usaha di Kecamatan Denpasar Selatan - Tri Astuty, Ni Nyoman Ayu Rani; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Cooperative is an entity that have participated in building a national economic, in order to realize an advanced society, fair and prosperous. The aim of this study was to analyze the effect of directly or indirectly, services and variety of products on the participation of members, and operating results (SHU) in business cooperatives in South Denpasar District. This study used two methods of analysis, namely factor analysis and path analysis. Factor analysis is used to obtain factor scores of latent variables formed by the indicator, while the path analysis is used to analyze the effect of directly or indirectly, services and variety of products on the participation of members and SHU. The analysis showed that services a significant effect on the participation of members and SHU, product variation does not significantly influence the participation of members and SHU. The participation of members of the mediating variables between services and SHU. Member participation is not a mediating variable between variety of products and SHU
Keywords: perekonomian, jasa pelayanan, variasi produk, partisipasi anggota, sisa hasil usaha